Determinação da atividade do rádio-226 em fosfogesso usado como adiação ao clínquer por meio de medidas de radônio-222 - Geraldo, Ricardo Rossasi (2021)
The use of phosphogypsum by the cement industry is a viable alternative to replace natural plaster in the production of clinker used in the manufacture of Portland cement and its use can result in economic benefits. This waste is a by-product generated on a large scale by the phosphate fertilizer industries during the production of phosphoric acid by the wet process. It is an environmental liability consisting of impurities such as fluorides, heavy metals in addition to presenting radionuclides from the 238U, 232Th series in addition to 40K in their composition. The storage of this input is done in the open in the vicinity of the producing industries, generating environmental impacts due to the pollution of groundwater and springs and soil degradation. One of the radioactive elements found in the phosphogypsum composition is the 226Ra precursor to 222Rn. These elements are responsible for the highest level of internal exposure to ionizing radiation that human beings are subjected to throughout their lives. Radon is a gas that when inhaled presents itself as a potential cause of lung cancer. Thus, the objective of this work was to measure the concentration of 222Rn using the AlphaGUARD detector (Saphymo GmbH) in plaster/phosphogypsum mortar and cement mortar with different compositions and from these concentrations to infer the activity concentration of 226Ra by applying a simplified physical-mathematical model. The values obtained by this method were compared to the values obtained by the gamma spectrometry technique in order to show the feasibility of using the simplified physical-mathematical model in determining the activity concentration of 226Ra in materials. The values of 226Ra activity concentration, measured in Bq/kg, obtained by the physical-mathematical model for the analyzed specimens were 6.2±0.8; 6.0±3.4; 10.0±5.1; 4.3±3.3 and 22000±43000, respectively. The values obtained by gamma spectrometry, in Bq/kg, were 8±2; 16.7±1.3; 8.8±0.7; 7.7±0.7 and 927±31, respectively. The values found for the 226Ra activity concentration by both techniques for the plaster/phosphogypsum mortar specimens and for the mortars are statistically equal, showing that the application of the simplified physical-mathematical model is an economically viable alternative in substitution gamma spectrometry in determining the concentration of 226Ra activity in materials. CNEN in its norm nº 147 establishes a limit value of 1000 Bq/kg for the 226Ra activity employed in the cement industry. Considering the values found for the activity concentration of this radionuclide because both techniques are well below the established limit, there are no restrictions for its use in the cement industry.